2015
DOI: 10.1007/s13237-015-0132-5
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive efficiency of two Luffa species - Factors affecting low reproductive rate in meiotically stable Luffa acutangula (L.) Roxb.

Abstract: Two species of genus Luffa, namely L. cylindrica and L. acutangula have been analyzed during the present study for the details of morphological and meiotic variability. While the former is found only in cultivation, the latter is cultivated on a small scale and also grows in wild in Jammu district of J&K state (India). These species match in their gross morphology and in having a diploid chromosome number of 2n=26. Of the two, L. acutangula is more efficient in its meiotic system displaying minimum abnormaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Length of the petiole flower ranged from one cm in Cucumis sativus to 27.5 cm in Lagenaria siceraria. These results are in harmony with Jamwal and Sharma (2015) who reported that Luffa cylindrical male and female flowers on the same plant with the lower nodes bearing only staminate flowers, followed by nodes having both staminate and pistillate flowers. Male flowers appeared first on the vine under staminate nodes, it was borne on a pedunculate raceme.…”
Section: Flowering Behaviorsupporting
confidence: 91%
“…Length of the petiole flower ranged from one cm in Cucumis sativus to 27.5 cm in Lagenaria siceraria. These results are in harmony with Jamwal and Sharma (2015) who reported that Luffa cylindrical male and female flowers on the same plant with the lower nodes bearing only staminate flowers, followed by nodes having both staminate and pistillate flowers. Male flowers appeared first on the vine under staminate nodes, it was borne on a pedunculate raceme.…”
Section: Flowering Behaviorsupporting
confidence: 91%
“…are domesticated [2,3]. Furthermore, L. cylindrica has always been a preferred crop for cultivation because of its higher fruit set and bigger fruit size [4]. This species is grown principally for production of sponges, which can be used as bath sponges, or as an alternative biomaterial used for packaging, furniture, and plastic appliances, and also as an adsorbent of heavy metal contaminants from industrial waters, which makes it a cash crop [4][5][6].…”
mentioning
confidence: 99%